Recent advances in Lynch syndrome - Li, Xi (Exp Hematol Oncol, 2021)
Lynch syndrome is one of the most common hereditary cancer syndromes and is characterized by the development of many cancers, such as colorectal cancer (CRC), endometrial cancer, ovarian cancer, stomach cancer and many other cancers. Lynch syndrome is caused by pathogenic germline variants in one of four DNA mismatch repair genes (MLH1, MSH2, MSH6, or PMS2) or by an EPCAM deletion. The MLH1 variant is correlated with the highest risk of CRC, while the MSH2 variant is correlated with the highest risk of other cancers. CRC is the most common cancer type that develops in individuals with Lynch syndrome, followed by endometrial cancer. Recent advances have been made to help us further understand the molecular pathogenesis of this disease and help improve diagnostic testing efficiency and surveillance strategies. Moreover, recent advances in immunotherapy provided by clinical trials also provide clinicians with more chances to better treat Lynch syndrome. This study aims to review many advances in the molecular genetics, clinical features, diagnosis, surveillance and treatment of Lynch syndrome.